2011
DOI: 10.1002/chp.20119
|View full text |Cite
|
Sign up to set email alerts
|

Pharmacist Web-Based Training Program on Medication Use in Chronic Kidney Disease Patients: Impact on Knowledge, Skills, and Satisfaction

Abstract: Pharmacists like the Web-based continuing education program. Over a short time span, the program improved their knowledge and skills. Its impact on their clinical practices and quality of medication use in CKD patients remains to be assessed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
0
2

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 24 publications
1
27
0
2
Order By: Relevance
“…Comparative studies assessing knowledge change demonstrated e-learning to be equivalent to lecture-based learning and superior to no training. 35,38,[41][42][43] One skills assessment reported significant gains (24% increase after training; adjusted compared to control), 35 while another reported superior skills after e-learning in a posttest compared to control. 41 Significant gains in selfperceived confidence or knowledge after e-learning varied in magnitude, depending on whether a 5-or 7-point rating scale was used.…”
Section: Resultsmentioning
confidence: 98%
See 4 more Smart Citations
“…Comparative studies assessing knowledge change demonstrated e-learning to be equivalent to lecture-based learning and superior to no training. 35,38,[41][42][43] One skills assessment reported significant gains (24% increase after training; adjusted compared to control), 35 while another reported superior skills after e-learning in a posttest compared to control. 41 Significant gains in selfperceived confidence or knowledge after e-learning varied in magnitude, depending on whether a 5-or 7-point rating scale was used.…”
Section: Resultsmentioning
confidence: 98%
“…Every study assessed a different learning topic, although 3 studies included diabetes within their focus. [30][31][32] Six studies (35%) assessed effectiveness of e-learning in pharmacists; [32][33][34][35][36][37] 10 studies (59%) assessed pharmacy students (of which 1 included preregistration pharmacists), 31,[38][39][40][41][42][43][44][45][46] and 1 study assessed both pharmacists and pharmacy students. 30 The number of participants in each study ranged from .…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations